Health care in pregnancy during the COVID‐19 pandemic and pregnancy outcomes in six low‐ and‐middle‐income countries: Evidence from a prospective, observational registry of the Global Network for Women's and Children's Health. (20th June 2022) - Naqvi, Seemab; Naqvi, Farnaz; Saleem, Sarah; Thorsten, Vanessa R.; Figueroa, Lester; Mazariegos, Manolo; Garces, Ana; Patel, Archana; Das, Prabir; Kavi, Avinash; Goudar, Shivaprasad S.; Esamai, Fabian; et al.
Abstract: Objective: To assess, on a population basis, the medical care for pregnant women in specific geographic regions of six countries before and during the first year of the coronavirus disease 2019 (COVID‐19) pandemic in relationship to pregnancy outcomes. Design: Prospective, population‐based study. Setting: Communities in Kenya, Zambia, the Democratic Republic of the Congo, Pakistan, India and Guatemala. Population: Pregnant women enrolled in the Global Network for Women's and Children's Health's Maternal and Newborn Health Registry. Methods: Pregnancy/delivery care services and pregnancy outcomes in the pre‐COVID‐19 time‐period (March 2019–February 2020) were compared with the COVID‐19 time‐period (March 2020–February 2021). Main outcome measures: Stillbirth, neonatal mortality, preterm birth, low birthweight and maternal mortality. Results: Across all sites, a small but statistically significant increase in home births occurred between the pre‐COVID‐19 and COVID‐19 periods (18.9% versus 20.3%, adjusted relative risk [aRR] 1.12, 95% CI 1.05–1.19). A small but significant decrease in the mean number of antenatal care visits (from 4.1 to 4.0, p  = <0.0001) was seen during the COVID‐19 period. Of outcomes evaluated, overall, a small but significant decrease in low‐birthweight infants in the COVID‐19 period occurred (15.7% versus 14.6%, aRR 0.94, 95% CI 0.89–0.99), but we did not observe any significant differences in other outcomes. There was no change observed in maternal mortality or antenatal haemorrhage overall or at any of the sites. Conclusions: Small but significant increases in home births and decreases in the antenatal care services were observed during the initial COVID‐19 period; however, there was not an increase in the stillbirth, neonatal mortality, maternal mortality, low birthweight, or preterm birth rates during the COVID‐19 period compared with the previous year. Further research should help to elucidate the relationship between access to and use of pregnancy‐related medical services and birth outcomes over an extended period.